HIV Treatment-As-Prevention Research: Authors’ Reply - Bärnighausen, Till (PLoS Med, 2015)
Till Bärnighausen and colleagues respond to comments by the HPTN 071 (PopART) Study Team, noting the distinction between the different HIV prevention questions the trial will attempt to answer.